Introduction to the Special Issue: Leadership in Kansas for the 21st Century - Randy Watson (Educational Considerations, 2016)
Kansas is currently experiencing a leadership challenge. This is evident both in the number of leaders new to their positions in K-12 school districts and in the methods our state must implement to effectively train those leaders for Kansas’ education to prosper into the 21st century.
Keywords: Leadership; Challenges; Kansas; education; United School Administrators; development